Cognitive Load Does Not Affect the Behavioral and Cognitive Foundations of Social Cooperation - Mieth, Laura; Bell, Raoul; Buchner, Axel (Frontiers in Psychology, 2016)
The present study serves to test whether the cognitive mechanisms underlying social cooperation are affected by cognitive load. Participants interacted with trustworthy-looking and untrustworthy-looking partners in a sequential Prisoner’s Dilemma Game. Facial trustworthiness was manipulated to stimulate expectations about the future behavior of the partners which were either violated or confirmed by the partners’ cheating or cooperation during the game. In a source memory test, participants were required to recognize the partners and to classify them as cheaters or cooperators. A multinomial model was used to disentangle item memory, source memory and guessing processes. We found an expectancy-congruent bias towards guessing that trustworthy-looking partners were more likely to be associated with cooperation than untrustworthy-looking partners. Source memory was enhanced for cheating that violated the participants’ positive expectations about trustworthy-looking partners. We were interested in whether or not this expectancy-violation effect—that helps to revise unjustified expectations about trustworthy-looking partners—depends on cognitive load induced via a secondary continuous reaction time task. Although this secondary task interfered with working memory processes in a validation study, both the expectancy-congruent guessing bias as well as the expectancy-violation effect were obtained with and without cognitive load. These findings support the hypothesis that the expectancy-violation effect is due to a simple mechanism that does not rely on demanding elaborative processes. We conclude that most cognitive mechanisms underlying social cooperation presumably operate automatically so that they remain unaffected by cognitive load.□